Synthesis of hierarchical ZnO&Graphene composites with enhanced photocatalytic activity. Issue 1 (January 2018) - Zhu, Linyu; Liu, Zirui; Xia, Pengfei; Li, Hong; Xie, Yahong
Abstract: A novel quasi core-shell structure of hierarchical ZnO coated with graphene, has been synthesized by a simple solvothermal method. After loading graphene on the surface of hierarchical ZnO, an intimate interfacial contact between them has been achieved. The experimental results indicate that hierarchical ZnO&Graphene composites (HZ&G) have large specific surface area, enhanced light harvesting in the visible light region, better separation efficiency and fast transfer rate of photo-generated carriers. Therefore, the HZ&G composites exhibit superior photocatalytic degradation efficiency over Rhodamine B (RhB) compared to pure hierarchical ZnO. Especially for HZ&G 15 composite with the nominal weight concentration of 15% GO, its removal rate of simulated pollutants is up to 98.5% under current experimental conditions. The primary reactive species in the process of photocatalytic RhB degradation is also confirmed by trapping experiments to be hydroxyl radicals (OH). Meanwhile, a probable mechanism of enhancement over photocatalytic RhB degradation has been proposed.